Ethanol Blend Effects on The Spray Properties of a Biodiesel Fuel by Ambient Pressure Variation - Nasrul Ilminnafik; Intan Hardiatama; Ahmad Adib Rosadi; Andi Sanata; Faiz Firdausi (Universitas Djuanda, 2023)
Diesel engine spray nozzles are crucial to pollutant generation and engine efficiency. Nozzle performance can be enhanced by adjusting the nozzle's internals. A successful demonstration of the nozzle would be one in which the spray's outcome was uniformly dispersed throughout a wide area, with the grains scattered similarly. The purpose of this research was to examine how a diesel-ethanol characteristic under normal atmospheric pressure (spray tip penetration, the velocity of spray, and spray angle) and, in general, to assess the performance of biodiesel fuel on diesel engines, a substantial amount of biodiesel and operational expenses for the engine are necessary. It was an experimental approach to the study. The research involved recording spray fuel at the nozzle. Using a 480 fps high-speed camera, we tested BD20, BD20E5, and BD20E10 fuel at three different ambient pressures (1 bar, 2 bar, and 3 bar). The injection pressure was 15 MPa, and the fuel temperature was 28.2 degrees Celsius. Spray tip penetration and spray velocity decreased and spray angle increased after ethanol was added to the mixture, consistent with the studies' findings. Lowered spray tip penetration, slower spray speeds, and a complete spray angle result from the increased ambient pressure.